2017
DOI: 10.1016/j.addbeh.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the link between alcohol expectancies and adolescent drinking

Abstract: Introduction Alcohol expectancies are important determinants and predictors of adolescent alcohol use. Research with African Americans has shown that the endorsement of positive alcohol expectancies differs from that of Whites during childhood and predicts different alcohol outcomes during young adulthood. However, limited research has explored racial differences in the relationship between expectancy endorsement and alcohol use in school-aged adolescents. The current study examines the effect of White or Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…No significant difference in the prevalence was found between the Akha and Lahu youths. This result coincides with that of the study of Banks et al among American adolescents aged 12-18 years in 2017, which found no difference in expectancies and consumption among different races [41].…”
Section: Discussionsupporting
confidence: 92%
“…No significant difference in the prevalence was found between the Akha and Lahu youths. This result coincides with that of the study of Banks et al among American adolescents aged 12-18 years in 2017, which found no difference in expectancies and consumption among different races [41].…”
Section: Discussionsupporting
confidence: 92%
“…Research is also sparse examining African American-White differences in the impact of alcohol expectancies on drinking outcomes. Evidence suggests a stronger effect of positive expectancies on alcohol use for White youth (Chartier, Hesselbrock, & Hesselbrock, 2009) with some researchers oberving a significant effect for White youth, but a null effect for African American youth (Banks & Zapolski, 2017;Meier, Slutske, Arndt, & Cadoret, 2007). This finding of a weaker effect of postive alcohol expectancies on drinking for African American youth may partially explain lower drinking outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, minorities tend to endorse similar rates of positive alcohol expectancies as Whites by early adolescence (Hipwell et al, 2005; Meier et al, 2007; Shih, Miles, Tucker, Zhou, & D’Amico, 2010). However, positive alcohol expectancies have been shown to have a stronger effect on adolescent drinking among White adolescents than minority adolescents (Banks & Zapolski, 2017; Chartier, Hesselbrock, & Hesselbrock, 2009; Meier et al, 2007). It is possible that this effect is explained by increased promotive factors among minority adolescents such as ethnic identity and negative alcohol expectancies.…”
Section: Discussionmentioning
confidence: 99%